PENYELESAIAN UTANG PIUTANG MELALUI PKPU DALAM PERKARA PERDATA NO .22/PDT.SUS-PKPU/2021/PN NIAGA MEDAN PADA PENGADILAN NEGERI MEDAN - Hanapi Sayuti Siregar (YAPEKAM, 2025)
Law Number 37 of 2004 concerning Bankruptcy and PKPU, which is a refinement, the position of PKPU is further strengthened in the Indonesian legal system as an instrument that is not only repressive, but also preventive against bankruptcy. This law provides a more comprehensive and operational legal basis for the implementation of PKPU, including the procedures for filing, appointing a supervisory judge, curator, and the time limit for the PKPU process. Thus, the existence of PKPU has strategic value in the business world because it allows companies to continue operating while completing their financial obligations through transparent and legally supervised restructuring. The problems in this paper are a) How to settle debts in Civil Case No. 22/Pdt.Sus-PKPU/2021/PN Niaga Medan at the Medan District Court, b). What are the judge's considerations in deciding debt cases through PKPU in Civil Case No. 22/Pdt.Sus-PKPU/2021/PN Niaga through PKPU. C). How is the legal certainty for PKPU applicants in obtaining their rights based on Law No. 37 of 2004. The research method used is normative legal research, namely research conducted by examining both primary and secondary legal materials. Normative legal research is used to study laws and regulations, doctrines, legal principles, and court decisions that are relevant to the problem of Postponement of Debt Payment Obligations (PKPU). The research findings are that the Panel of Judges in their decision, stated that the applicants' application was sufficiently legally based and fulfilled the elements as stipulated in Article 222 paragraph (1) of Law Number 37 of 2004, namely: The Respondent has more than one creditor; There is a debt that has matured and can be collected; Collection has been carried out both verbally and in writing; There has been a default by the respondent. Bankruptcy. The legal considerations of the panel of judges in PKPU cases are based on the fulfillment of formal and material requirements for submitting PKPU. Simple evidentiary elements, the existence of debt due, more than one creditor, and the good faith of the applicants are the main basis for accepting this application. With the understanding and application of these elements, the Commercial Court plays a role as an enforcer of justice in maintaining a balance between the legal protection of creditors and the debtor's business rights. Legal certainty in the PKPU process also concerns the clarity of debt status, both in terms of maturity, amount, and validity of the debt agreement. Article 8 paragraph (4) of Law No. 37 of 2004 even states that evidence in PKPU cases is sufficient to be carried out simply, namely by showing that the debtor has two or more creditors and there is a debt that is due and collectible.